Interpretation of bottom-hole temperature data from CO2 injection projects. (October 2020) - Mishra, Srikanta; Keister, Laura; Mawalkar, Sanjay
Highlights: Analysis uses amplitude of BHP and BHT changes during the preceding injection event, in conjunction with a temperature Horner plot. Workflow produces estimate of slope of pressure Horner plot which can be used to calculate permeability. Abstract: Although bottom-hole temperature (BHT) data is routinely collected with bottom-hole pressure (BHP) data during CO2 injection in geological storage projects, it is seldom analyzed in a quantitative manner. However, the BHP and BHT signals do exhibit correlated behavior. This study proposes a practical approach for using BHT data from warmback (no injection) periods, in conjunction with the amplitude of BHP and BHT changes during the preceding injection event, to estimate formation permeability. The methodology is demonstrated using data from the AEP Mountaineer project in USA where CO2 injection was carried out into a saline aquifer. Estimated permeability values from the proposed approach are in good agreement with those obtained from transient pressure analysis of BHP data from the falloff period.